1984
DOI: 10.1152/ajpheart.1984.247.1.h25
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of adenine nucleotide translocase in O2-deficient hearts

Abstract: At subsaturating concentrations of palmitoyl-CoA, the carnitine-dependent oxidation of the palmitoyl portion by uncoupled rat heart mitochondria was stimulated by ADP or ATP. This effect was traced to the prevention of acyl-CoA binding to adenine nucleotide translocase and the consequent sparing of acyl-CoA for acylcarnitine formation. Palmitoyl-CoA oxidation was stimulated by ITP also although ITP served neither as a transportable substrate nor as an inhibitor of ADP transport. ITP and other nontransportable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, increased levels of long chain FAs have also been suspected to be involved in unexplained sudden death in infants with conduction defects or ventricular fibrillation and tachycardia [59]. In addition to LCAC accumulation, acute ischemia is also associated with a decreased ANT activity, independently of any change in oxidative phosphorylation, [60][61][62] and an increased RyR2 oxidation leading to reperfusion injury [63]. Similarly, PC level was shown to correlate with NYHA classification and high plasma levels of PC were significantly associated with serious adverse events and poor prognostic of heart failure patients [64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased levels of long chain FAs have also been suspected to be involved in unexplained sudden death in infants with conduction defects or ventricular fibrillation and tachycardia [59]. In addition to LCAC accumulation, acute ischemia is also associated with a decreased ANT activity, independently of any change in oxidative phosphorylation, [60][61][62] and an increased RyR2 oxidation leading to reperfusion injury [63]. Similarly, PC level was shown to correlate with NYHA classification and high plasma levels of PC were significantly associated with serious adverse events and poor prognostic of heart failure patients [64].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Nagarse pretreatment had no noticeable effect on the carboxyatractyloside-insensitive (to eliminate contribution of the acyl-CoA binding on the adenine nucleotide translocase, the major IM binding site; ref. 36) or -sensitive binding of octanoyl-CoA to mitochondria. The latter was also not affected by the presence of malonyl-CoA.…”
Section: Biochemistry: Murthy and Pandementioning
confidence: 99%
“…Since adenine nucleotide transport is electrophoretic (Klingenberg, 1975), the decrease in protonmotive force following deenergisation is accompanied by a backflow of cytosolic ATP into the matrix where it is hydrolysed by H+-ATPase to restore the protonmotive force. Pande et al (1984) have suggested that adenine nucleotide translocase protects the hypoxic heart from failure by building large amounts of cytosolic LCA thus preventing the increase of mitochondrial acylcarnitine and LCA which were believed to cause mitochondrial damage. The dramatic increase in mitochondrial LCA prevents breakdown of the heart during hypoxia by inhibiting transport of ATP back into the mitochondria.…”
Section: Regulation Of Uncoupling Protein and Formation Of Thermogenimentioning
confidence: 99%